Adhesion Properties Of Benzoly Peroxide Crosslinked Epoxidized Natural Rubber (ENR 25) - Based Pressure Sensitive Adhesives - Suid, Nurul Hamiza (2014)
The objective of this study was to evaluate the influence of crosslinking density, rate of testing and thickness coating on the adhesion properties of epoxidized natural rubber (ENR 25)-based adhesives using coumarone-indene, gum rosin and petroresin as the tacki fiers. Toluene and polyethylene terephthalate (PET) were used as solvent and coating substrate respectively. A SHEEN hand coater was used to coat the adhesive on the substrate. All adhesion properties were determined by a LJyod Adhesion Tester operating at different rates of testing. Results showed that the adhesion properties of ENR 25-based adhesive increased with crosslink density and reduced again after the optimum crosslink. The loop tack and peel strength of cournarone-indene, gum rosin and petroresin passed through a maximum value at I parts per hundred parts of rubber (phr), 2 phr and 3 phr benzoyl peroxide concentration respectively, an observation which was attributed to the optimum crosslinking of ENR 25 where optimum cohesive and adhesive strength was obtained.